Results of posterior lamellar femto-keratoplasty using two different lasers - B. E. Malyugin; A. N. Pashtaev; N. F. Shilova; K. N. Kuzmichev; K. I. Katmakov (Офтальмохирургия, 2021)
Purpose. To evaluate the results of treatment of patients with pseudophakic bullous keratopathy (PBK) by the method of posterior lamellar femto-keratoplasty with ultrathin graft (FS-DSEK) harvested using two different lasers.Material and methods. The results of surgical treatment of 82 patients (82 eyes) underwent posterior lamellar femto-keratoplasty for PBK were analyzed. In the 1st group included 43 patients (43 eyes) with PBK underwent FS-DSEK using FS laser Femto-Visum (Optosystems, Russia). In the 2nd group included 39 patients (39 eyes) with PBK underwent FS-DSEK using LDV Z8 (Ziemer, Switzerland). Observation period was 1 year. Before and after surgery following indicators were evaluated: uncorrected visual acuity (UCVA), best spectacle corrected visual acuity (BSCVA), postoperative astigmatism, central corneal thickness (CCT), graft thickness, center-periphery (C:P) ratio, endothelial cell density (ECD), endothelial cell (EC) loss, optical density .Results. Transparent engraftment at 1-year observation period was observed in 88% of cases. In the 1st group UCVA=0.22±0.11, BSCVA=0.32±0.12, in the 2nd group UCVA=0.18±0.08, BSCVA=0.29±0.1 (p>0.05). The maximum BSCVA in both groups was 0.6. Postoperative astigmatism was comparative in 2nd groups – 1.43±1.1 and 1.38±1.0 D, respectively (p>0.05). In the 1st group, CCT=549±31, graft thickness in the central zone – 83±12, C:P ratio – 0.92±0.05; in the 2nd group CCT=546±28, graft thickness – 80±10, C:P ratio – 0.94±0.06 (p>0.05). In the 1st group ECD – 1326±282, EC loss – 55±6%; ECD in the 2nd – 850±230, EC loss – 70±7% (p<0.05). According to the results of densitometry, optical density of the posterior layers of the cornea and «donor–recipient» interface zone was higher in the 2nd group, both in the central and in the paracentral zones: in the 1st group in the posterior layers of the stroma – 16.4±1.2 (0–2 mm) and 15.8±1.0 (2–6 mm), in the interface zone – 14.5±0.9 (0–2) and 13.9±0.8 (2–6), in the 2nd group in the posterior layers – 18.3±1.3 (0–2 mm) and 17.9±1.1 (2–6 mm), and in the interface zone – 17.3±1.2 (0–2 mm) and 17.0±1.0 (2–6 mm, p<0.05).Conclusions. FS-DSEK showed high efficiency for treating patients with PBK. Functional results were comparative in 2nd groups. Statistical analysis showed highest safety of transplanted endothelium in the 1st group at 1-year observation period.